PERILAKU KONSUMEN DALAM MEMBELI PRODUK HALAL PADA MAHASISWA DI KOTA BENGKULU - Annisah Monica Juliyanti; Rheesty Illahyana; Zul Fikri; Asnaini Asnaini; Herlina Yustati (Universitas Darussalam Gontor, 2021)
Especially in the city of Bengkulu, there are two types of universities. In this research, the main attraction is PTKIN Bengkulu State Islamic Institute and PTN Bengkulu University. Based on observations made by researchers, it gives an attraction that some students from Bengkulu University have very detailed consumer behavior towards halal products, while knowledge about the definition of halal products is not so deeply discussed in their lecture world. Meanwhile, there are several students from the Bengkulu State Islamic Institute who are already well-known for their universities based on the Islamic religion, but are still not very detailed in the selection of halal products. By using a quantitative approach method based on the type of primary data through observation techniques with a sample of 132 FEBI IAIN students and 132 FEB UNIB students in Bengkulu City. Based on the results of the t-test calculation, the t-value is 1.42. Furthermore, thet value iscalculated compared with the ttable, which is 2.01. Based on the results of tarithmetic in this study, it is known that tcount < ttable is 1.42 < 2.01, so there is no significant difference in the consumption behavior of halal products in students of FEBI IAIN Bengkulu and FEB UNIB, although the groups of students who come from different scientific bases namely from Islamic universities and the general public did not show significant differences in consuming the product.